2015
DOI: 10.11124/jbisrir-2015-1876
|View full text |Cite
|
Sign up to set email alerts
|

Routine culture-based screening versus risk-based management for the prevention of early-onset group B streptococcus disease in the neonate: a systematic review

Abstract: The results of this review come from nine studies published in peer reviewed journals. The treatment group consists of those screened as per the culture-based protocol, the control group the risk-based protocol. For combined term and preterm infants the odds of early-onset group B streptococcus disease for the treatment vs control groups is 0.45 (95% CI 0.37 to 0.53). The odds ratio in term infants is 0.45 (95% CI 0.36 to 0.57). Preterm infants are four times (OR 4.20 [95% CI 3.36 to 5.24]) more likely to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…A systematic review of nine observational studies from Turkey, Australia, and the US found that the odds of early onset GBS infection under universal screening were 55% lower than under risk based prevention for all neonates and for term neonates (three studies) 80. A 2017 study in a UK maternity unit found that the rate of early onset GBS infection fell from 0.99 per 1000 live births in the risk based period to 0.33 per 1000 in the screening period, although this was not statistically significant, and screening was instigated based on high incidence so there may have been regression to the mean 81.…”
Section: Uncertain Evidence On Screening Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of nine observational studies from Turkey, Australia, and the US found that the odds of early onset GBS infection under universal screening were 55% lower than under risk based prevention for all neonates and for term neonates (three studies) 80. A 2017 study in a UK maternity unit found that the rate of early onset GBS infection fell from 0.99 per 1000 live births in the risk based period to 0.33 per 1000 in the screening period, although this was not statistically significant, and screening was instigated based on high incidence so there may have been regression to the mean 81.…”
Section: Uncertain Evidence On Screening Effectivenessmentioning
confidence: 99%
“…Risk of bias is higher in these studies because participants in the two arms are not contemporaneous, so other differences between these periods may contribute. The few observational studies that compare screening with concurrent controls often retrospectively compare women who have a culture result to all other women8990; this may be biased due to the risk of misclassification and because people who accept screening are systematically different from those who do not 8091. Finally, as most studies only assess early onset GBS infection confirmed on culture, changes in disease incidence may actually reflect a decreased likelihood of culturing GBS in the laboratory, owing to the presence of antibiotics in neonates’ blood 92.…”
Section: Uncertain Evidence On Screening Effectivenessmentioning
confidence: 99%
“…In another study, differing succession of bacterial community was observed between IAP exposed and control full-term infants [35]. In fact, women who are to receive IAP are indicated to have at-risk pregnancies and more likely to undergo a series of interventions such as increased hospitalization [36].…”
Section: Sanitization Of Birth: Antibiotics During Vaginal Birthmentioning
confidence: 98%
“…The main concern with risk-factor screening is timely identification of the risk so that antibiotics can be administered [12]. The incidence of EOGBSD in settings that use this method of screening is 0.5/1000 live births [13].…”
Section: Risk-factor Screeningmentioning
confidence: 99%